Características físicas e hidráulicas del pavimento rígido existente en la vía Balbanera – Pallatanga en la provincia de Chimborazo - Sanipatín Chiluiza, Michael Raúl (2024)
The state highways of Ecuador interconnect various regions, geological zones, and climatic belts, resulting in variations in the stratigraphic profile upon which they are built. This research has evaluated the primary physical and hydraulic characteristics of the existing rigid pavement on the Balbanera – Pallatanga route using core extraction and infiltration methods. Through a series of laboratory tests such as granulometric analysis, indirect tensile and core compression tests, along with in-situ evaluations for gathering significant data, the performance and quality of the pavement in question were assessed. The results obtained offer detailed insights into key aspects such as water absorption, moisture levels, infiltration capacity, and runoff coefficient, aiding in the identification of areas for improvement and formulation of recommendations to effectively address the current road challenges in the mentioned corridor. This study not only sheds light on the current pavement situation but also lays the groundwork for future research and corrective actions aimed at optimizing the road infrastructure and ensuring the safety and efficiency of the transportation network in the region.